Ion-intercalation mechanism and structural relaxation in layered iron phosphate Na3Fe3(PO4)4 cathodes - Jakobsen, Christian Lund; Johansen, Morten; Ericsson, Tore; Häggström, Lennart; Christensen, Christian Kolle; Nielsen, Ida; Brant, William Robert; Ravnsbæk, Dorthe Bomholdt (Frontiers in Batteries and Electrochemistry, 2024)
Layered Na3Fe3(PO4)4 can function as a positive electrode for both Li-and Na-ion batteries and may hold advantages from both classical layered and phosphate-based electrode materials. Using a combination of ex-situ and operando synchrotron radiation powder X-ray diffraction, void space analysis, and Mössbauer spectroscopy, we herein investigate the structural evolution of the Na3Fe3(PO4)4 framework during Li-and Na-ion intercalation. We show that during discharge, Li-and Na-intercalation into Na3Fe3(PO4)4 occurs via a solid solution reaction wherein Na-ions appear to be preferentially intercalated into the intralayer sites. The intercalation causes an expansion of the unit cell volume, however at open circuit conditions after ion-intercalation (i.e., after battery discharge), Na3+xFe3(PO4)4 and LixNa3Fe3(PO4)4 undergo a structural relaxation, wherein the unit volume contracts below that of the pristine material. Rietveld refinement suggests that the ion intercalated into the intralayer sites diffuse to the sites in the inter-layer space during the relaxation. This behavior brings new perspectives to understanding structural relaxation and deviations between structural evolution observed under dynamic and static conditions.